Comparative Study of Nahdlatul Ulama (NU) Ma'arif Educational Institution with Muhammdiyah Institution - Muhamad Rikza Saputro; Sukiman Sukiman (Cita Konsultindo Research Center, 2023)
This study aims to determine the comparison between the Nahdlatul Ulama (NU) Ma'arif educational institution and the Muhammadiyah educational institution. Actually, the two institutions are equally good and their usefulness can be felt by every Muslim and Muslim woman. But each educational institution certainly has its own differences. This study aimed to find out how the Nahdlatul Ulama (NU) Ma'arif educational institution compares with Muhammadiyah educational institutions. Thus, the author is interested in discussing the comparison or comparison of the two educational institutions. This research uses qualitative methods through two approaches, namely literature studies. The study is described descriptively, as well as explained systematically. The results of the literature study show that the preparation between Muhammadiyah Educational Institutions and Nahdlatul Ulama (NU) Educational Institutions, when viewed in terms of deepening the content of the material at the Nahdlatul Ulama (NU) educational institution, is superior because it can be said that Islamic Religious Education in Nahdlatul Ulama (NU) is delivered twice through nu-an subjects and for the Islamic Religious Education subject itself.